Preterm Birth Affects Early Motor Development in Pigs - Vanden Hole, Charlotte; Ayuso, Miriam; Aerts, Peter; Van Cruchten, Steven; Thymann, Thomas; Sangild, Per Torp; Van Ginneken, Chris (Frontiers in Pediatrics, 2021)
Background: Preterm infants frequently show neuromotor dysfunctions but it is not clear how reduced gestational age at birth may induce developmental coordination disorders. Advancing postnatal age, not only post-conceptional age, may determine neuromuscular development, and early interventions in preterm newborns may improve their later motor skills. An animal model of preterm birth that allows early postnatal detection of movement patterns may help to investigate this hypothesis. Methods: Using pigs as a model for moderately preterm infants, preterm (106 d gestation, equivalent to 90% of normal gestation time; n=38) and term (115 d gestation, equivalent to 99% of normal gestation time; n=20) individuals were delivered by caesarean section and artificially reared until postnatal day 19 (pre-weaning period). The neuromotor skills of piglets were documented using spatio-temporal gait analyses on video recordings of locomotion at self-selected speed at postnatal age 3, 4, 5, 8 and 18 days. Results were controlled for effects of body weight and sex. Results: Both preterm and term piglets reached mature neuromotor skills and performance between postnatal days 3-5. However, preterm pigs took shorter steps at a higher frequency, than term piglets, irrespective of their body size. Within preterm pigs, males and low birth weight individuals took the shortest steps, and with the highest frequency. Conclusion: Postnatal development of motor skills and gait characteristics in pigs delivered in late gestation may show similarity to the compromised development of gait pattern in preterm infants. Relative to term pigs, the postnatal delay in gait development in preterm pigs was only few days, i.e. much shorter than the 10-day reduction in gestation length. This indicates rapid postnatal adaptation of gait pattern after reduced gestational age at birth. Early life physical training and medical interventions may support both short- and long-term gait development after preterm birth in both pigs and infants.